2004
DOI: 10.1111/j.1600-0501.2004.01053.x
|View full text |Cite
|
Sign up to set email alerts
|

Titanium release from implants prepared with different surface roughness

Abstract: At a level relevant for commercial oral implants, no correlation was found between increasing roughness and ion release, neither in vitro nor in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
2
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 26 publications
2
82
2
6
Order By: Relevance
“…This value is extremely small and is safely below the citotoxicity level of Ti, reported as 5 ppm [44].The respective corrosion rate for the basal planes of nanostructured Ti is estimated as ~1.65 g cm -2 year -1 or 0.03 g cm -2 week -1 . Usually, the released Ti is found in much larger concentrations in tissues at close distance to the implant (≤1000 m) than in blood or saliva (Table 6), therefore it is safe to assert that the release rate measured in this work improves various reported values [45][46][47][48][49] …”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 51%
“…This value is extremely small and is safely below the citotoxicity level of Ti, reported as 5 ppm [44].The respective corrosion rate for the basal planes of nanostructured Ti is estimated as ~1.65 g cm -2 year -1 or 0.03 g cm -2 week -1 . Usually, the released Ti is found in much larger concentrations in tissues at close distance to the implant (≤1000 m) than in blood or saliva (Table 6), therefore it is safe to assert that the release rate measured in this work improves various reported values [45][46][47][48][49] …”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 51%
“…No negative effects from aluminum (Al) ions were seen on the peri-implant bone tissues, even if blasted surfaces contained a significant amount of aluminum, most probably because with blasted implants only a limited and transient release of Al ions occurs. 32 Wennerberg et al 33 found no correlation between ion release and surface roughness levels of commercial implants.…”
Section: Implant Microdesignmentioning
confidence: 98%
“…(a) Sand-blasted largegrit acid-etched (SLA), which involves sandblasting followed by acid etching and then dry-storage in air within sterile packaging. Moderate roughness can promote cellular differentiation and osteogenesis, [15][16][17][18][19] while surface energy/ wettability provides the driving force for bone cell adhesion and proliferation and reinforces matrix protein adsorption, ultimately affecting the quality of the osseointegration of the implant. 13,14 These two methods generate different surface structures, which result in different surface roughnesses and energy/wettability.…”
Section: Introductionmentioning
confidence: 99%